Taguchi's Methodology for Determining Optimum Operating Conditions in Hydrothermal Pretreatments Applied to Canola Seeds - Fernández, María Belén (2014)
The aim of the present work was to determine the operational optimum conditions in hydrothermal pretreatments applied to canola seeds. The effect of these pretreatments on the canola oil extraction yield and quality was evaluated. Sample was characterized by proximal analysis. As determinations of oil quality, acidity and peroxide value, tocopherol content and acidic composition were studied. Seeds were exposed to direct vapor in an autoclave. Pretreatments were carried out using different condition of temperature (100, 120 and 130°C), exposition time (5, 15 y 30 min) and seed granulometry (milled seeds, with a particle size in a range from 0.420 mm to 1.000 mm; broken seeds, with a particle size ranging from 1.000 mm to 1.410 mm and entire seeds). After each hydrothermal pretreatment, oil extraction yield was obtained with the Soxhlet method (hexane). The Taguchi methodology was followed in order to explore the operational optimum conditions selecting the most favorable levels of each variable, using an L9 experimental design. Initial oil content was 44.2 % dry basis (db). The best values of oil yield and quality were obtained when a temperature of 120°C, a time of 5 min and broken seeds were used. The optimum experiment generated an oil yield increment of 25% respect to the not hydrothermally-treated seed, meanwhile quality parameters remained within the commercialization values accepted.